Ultra-processed food intakes associated with 'food addiction' in young adults. (1st November 2022) - Whatnall, Megan; Clarke, Erin; Collins, Clare E.; Pursey, Kirrilly; Burrows, Tracy
Abstract: Exploring potentially addictive foods and food components is a recent research focus. Few studies have evaluated this based on level of food processing using the NOVA classification system. This study compared intakes of ultra-processed foods in young adults with and without food addiction. Secondary analysis of online cross-sectional survey data was conducted. The sample included 735 young Australian adults (18–35 years). Dietary intake was assessed by food frequency questionnaire and coded using NOVA to determine percentage energy (%E) from each of the four NOVA categories (unprocessed; processed culinary ingredients; processed; ultra-processed). Food addiction was assessed using the Yale Food Addiction Scale (YFAS). Linear regression models, adjusted for age, gender and body mass index (BMI), were developed to examine the association between %E from NOVA categories with food addiction status and number of symptoms. Sample mean age was 24.7 ± 4.2 years, 85% were female, 67% within healthy weight BMI range, and 20% classified as food addicted. Participants consumed 34.3 ± 13.4 %E from ultra-processed foods. Young adults classified as food addicted consumed a higher %E from ultra-processed foods (β = 3.954, p = 0.002) and a lower %E from unprocessed foods (β = −2.743, p = 0.010) than those classified as not food addicted. For each additional food addiction symptom reported, the %E from ultra-processed foods was higher (β = 1.693, p < 0.001) and %E from unprocessed foods was lower (β = −1.238, p < 0.001). Results demonstrate an association between YFAS assessed food addiction and higher intakes of ultra-processed foods, providing an important new perspective on the relationship between self-reported diet and food addiction in young adults. Future research should evaluate the relationship between food addiction, ultra-processed food intakes and health in longitudinal studies in order to inform potential treatment approaches.